The Effect of Circulo Massage on Changes in Blood Pressure in HypertensionPatients - Ardhiyansyah Cahya Wardana; Anggita, Gustiana Mega (Journal of Sport Science and Fitness, 2025)
Introduction: Human health is the main key in carrying out activities or life activities. Humans will not always have a strong and healthy body as they age and will experience a decline in the ability of body functions. One of the physical changes that occurs is increased blood pressure or hypertension. Hypertension is a condition or conditions in which a person experiences an increase in blood pressure above normal limits that can cause pain and even death. A person is said to have hypertension if the blood pressure exceeds the normal limit, which is > 140/90 mmHg. Overcoming hypertension can be done in a variety of ways. Objectives: One of the efforts to reduce hypertension is to provide circulo massage treatment, which is one of the masse techniques that aims to improve peripheral blood circulation so as to help the recovery process and manage the rest of the body's metabolism and provide relaxation to the muscles and nerves. Method: The type of research used is with quantitative descriptive research methods. The research design uses the Pre-experimental design method. The research sample is part of the population. The sampling technique in this study uses total sampling, that is, the entire population is taken as a sample and the researcher does not determine the minimum size of the research sample. The sample in this study is 30 people. The instrument used to measure blood pressure is using a digital sphygmomanometer, to measure blood pressure both before and after the massage treatment. The data analysis techniques in this study are by normality test, homogeneity test, and difference test. Result: The results showed that the decrease in systole blood pressure from the average before the massage with the Circulo massage technique was 146.63 mmHg and after the Circulo massage the average systole blood pressure was 129.233 mmHg, so there was a change in the decrease of 17.4 mmHg. The decrease in diastole blood pressure from the average before the massage with the Circulo massage technique was 92.43 mmHg and after the Circulo massage the average diastole blood pressure became 80.90 mmHg, so there was a change in the decrease of 11.53 mmHg. Conclusion: It was concluded that there was a significant effect of circulo massage on changes in blood pressure in hypertensive patients in Yogyakarta therapy houses. Advice to hypertension sufferers in the Bantul Yogyakarta area in particular and the wider community in general that it is necessary to check blood pressure and pulse regularly so that it can be well controlled and can make circulo massage an alternative treatment.